Nursing students’ perceived stress and influences in clinical performance - Akhu-Zaheya, Laila; Shaban, Insaf; Khater, Wejdan (International Journal of Advanced Nursing Studies, 2015)
Background: It is known that stress related to clinical training among nursing students could contribute to many physical and mental problems. However, little empirical evidence about the influence of stress in nurse students’ clinical performanceObjective: The objective of this study was to assess the association between perceived stresses, stress related factors, and students’ clinical performance.Method: Using the perceived stress scale, 539 Jordanian nursing students from 2 public universities in Jordan participated in the study.Results: The results showed that the mean of stress perceived by students was 45.9. Students’ assignment were perceived as the main source of stress (M= 10.7, SD= 4.5) followed by stress related to patients’ care (M= 10.5, SD= 5.5) and stress from teachers and nursing staff (M= 9.6, SD= 5.3). The lowest source of stress is from students’ lack of professional knowledge and skills (M= 3.96; SD= 2.8). The mean of students’ clinical performance is 73.4%. Students’ perceived stress has a significant negative correlation with students’ clinical performance (r= -.09; p
Keywords: Nursing Students; Nursing Education; Stress; Clinical; Practice.